Approximate Likelihood Estimation of Divergence Time Range Using a Coalescent-based Model. (January 2013) - RoyChoudhury, Arindam
We present an estimation of divergence time-range based on a coalescent model. This model sum the probability of coalescent trees, taking into account the effect of incomplete lineage sorting. Maximum likelihood estimate based on this model has been computed previously; however, a formula for divergence time-range estimate or confidence interval has never been presented for this model as the expression of the likelihood makes this estimation difficult to compute. Our formula for the divergence time-range estimate can be readily coded into a program. We did not use a simulation or resampling-based approach and therefore our method is fast and less computationally intensive. We demonstrate that our method is much faster and as accurate a simulation-based approach.